How sulfadoxine-pyrimethamine (SP) was perceived in some rural communities after phasing out chloroquine (CQ) as a first-line drug for uncomplicated malaria in Tanzania: lessons to learn towards moving from monotherapy to fixed combination therapy - Nsimba Stephen ED (BMC, 2006)
Abstract Malaria is a leading cause of death in Sub-Saharan Africa. Tanzania changed its malaria treatment policy from chloroquine (CQ) to Sulphadoxine-Pyrimethamine (SP) as first line drug in August 2001. We wanted to assess the perception and behaviour about SP after phasing out chloroquine which was very popular, cheap, available, and was preferred by many people for self-medication in homes as it was considered to have minimal side effects. Focus Group Discussions (FGDs) were carried out after one year of the anti-malarial drug treatment policy change in the country. The FGD themes were on malaria for under-five children and other age groups, anti-malarial drug use through self-medications, specific experiences people had about SP drug for both mothers/guardians, men in the communities and health workers. A total of twelve FGDs were performed with mothers/guardians, men and health workers in the selected public health care facilities in the district. In the FGDs people feared adverse reactions from SP; its slow ability of reducing fever and self-treatment in this case was less reported from the mothers/guardians groups. However, SP was reported by health workers to be administered using the direct observation approach under supervision in their health care facilities. This was done in order to increase compliance as there were worries that some mothers were throwing away the drug if they were instructed by health workers to go and administer SP to their sick children at home. Based on this information, it is obvious that fear and negative perceptions about SP drug was common in the study setting. As evidence of this, there was less reported home-stocking and self-medication in the discussions for this particular recommended new first-line anti-malarial. The public has demonstrated a lack of confidence in SP. Furthermore, some health workers expressed obvious fear and negative perceptions towards the drug despite the fact that some FGDs with health workers considered the drug to be good and effective against malaria. Such negative perception towards SP highlights the need to start earlier sensitization and educational campaigns to the rural communities for a new drug program to ensure its success. Messages should clearly state what should be expected from the new drug (Coartem), before its introduction. This is important especially as Tanzania is expected to move towards the expensive but efficacious and effective fixed-combination (Coartem) anti-malarial therapy early next year (2006).